Maryland Power Plant Cooling-Water Intake Regulations and their Application in Evaluation of Adverse Environmental Impact - Richard McLean; William A. Richkus; Stephen P. Schreiner; David Fluke (The Scientific World Journal)
Maryland’s cooling-water intake and discharge regulations, the Code of Maryland Regulations (COMAR) 26.08.03, stem from Sections 316(a) and (b) of the Clean Water Act (CWA). COMAR 26.08.03.05 and litigative and administrative rulings stipulate that the location, design, construction, and capability of cooling-water intake structures must reflect the best technology available (BTA) for minimizing adverse environmental impacts (AEIs), providing that the costs of implementing the BTA are not wholly disproportionate to the expected environmental benefits. Maryland law exempts facilities that withdraw less than 10 million gallons/day (MGD) and less than 20% of stream or net flow by the intake. If not exempt, BTA must be installed if the cost of doing so is less than five times the value of fish impinged annually. Through site-specific studies and the use of a Spawning and Nursery Area of Consequence (SNAC) model applied to Representative Important Species, several power plants were evaluated to determine if they have had an adverse effect on spawning and nursery areas of consequence. Examples of application of the Maryland law to a number of power plants in the state are presented, together with the outcome of their evaluation.